Gap surface plasmon-enhanced photoluminescence from upconversion nanoparticle-sensitized perovskite quantum dots in a metal–insulator–metal configuration under NIR excitation. Issue 2 (17th December 2021) - Kim, Minju; Kim, Youngji; Kim, Kiheung; Huang, Wen-Tse; Liu, Ru-Shi; Hyun, Jerome K.; Kim, Dong Ha
Abstract : 29-Fold luminescence enhancement of upconversion nanoparticle-sensitized perovskite quantum dots was achieved by implementing a metal–insulator–metal configuration and plasmonic coupling. Abstract : Very high luminescence enhancement of perovskite quantum dots (PeQDs) is achieved under near-infrared excitation through sensitization by upconversion nanoparticles (UCNPs) and localized surface plasmon (LSP) coupling. To overcome the low quantum yield of UCNPs, the plasmonic effect is exploited through a metal–insulator–metal (MIM) configuration. Here, Au nanorods (AuNRs) on a UCNPs/PeQDs (UP) layer supported by a Ag film (AuNRs–UCNPs/PeQDs–Ag film, or MUPM) configuration using UCNPs and PeQDs of similar sizes as the insulator layer is reported for the first time. Despite the thin thickness of the UP layer, we observed strong green emission from the PeQDs under 980 nm excitation, indicating high energy transfer efficiency. Furthermore, by capping AuNRs with amphiphilic diblock copolymers, photoluminescence quenching is suppressed. An overall 29-fold upconversion enhancement is achieved for the green emission in the MUPM compared with a UCNPs/PeQDs–glass owing to the strongly localized electric field from gap surface plasmons and the coupling of the longitudinal LSP resonance band of AuNRs with the excitation of UCNPs. This study provides a novel pathway to prepare a highly efficient and effective emissive device based on MIM configurations using UCNPs and PeQDs, which can be expanded to serve as a generalized platform in a wide range of optoelectronic applications.